Theoretical analysis and validation of a refrigeration system with phase change material (PCM) integration - Noya, Tuğçe (My University, 2020)
Bu çalışmada, soğutma deneyleri gerçekleştirmek için bir test ekipmanı tasarlanmış ve oluşturulmuştur. PCM olan ve olmayan durumlar için sistem performansları deneysel olarak belirlenmiş ve karşılaştırılmıştır. Ayrıca test prosedürünün matematiksel bir modeli oluşturulmuştur. Sayısal model sistem performansını sayısal olarak incelemeyi ve farklı çalışma koşulları için deney sonuçlarını tahmin etmeyi amaçlamaktadır. Model ve testler arasındaki doğrulama sonuçları, önerilen modelin sistemin deneysel verileriyle uyum sağladığını göstermektedir. PCM entegrasyonu ile kompresör kapanma süresinde elde edilen uzama, PCM'siz duruma göre yaklaşık % 16.7 daha fazla enerji tasarrufu sağlamıştır. Kompresörün her bir çalışma çevrimi için çalışma süresi oranı % 26’dan % 22’ye düşürülmüştür. Ayrıca, sistem için elektrik kesintisi senaryoları simüle edilmiş ve 0.2 saat elektrik kesintisi için 600 ml PCM ile en etkili enerji tasarrufu sonucu elde edilmiştir.Bu nedenle, PCM entegre soğutma sistemlerinin kullanımına dayanan deneysel ve sayısal araştırmalar çok önemlidir. Bu tür çalışmaların, geleneksel soğutma sistemlerinin kullanımıyla ilgili küresel ve yerel sorunların çoğunun üstesinden geleceği düşünülmektedir.

In this study, a test rig was designed and installed to perform refrigeration experiments. System performances for the cases with and without PCM were determined experimentally and compared. Besides, a mathematical model of the test procedure has been proposed. The numerical model aims to examine the system performance numerically and predict the experimental results for different operating conditions. The verification results between the model and test show that the proposed model has a good agreement with the experimental data of the system. The achieved prolongation in compressor off time with PCM integration provided energy-saving about % 16.7 more compared to the case of without PCM. Running time ratio of the compressor was reduced from % 26 to % 22 for one cycle of the compressor by PCM integration. Additionally, power failure scenarios were simulated for the system and the most effective energy-saving result was obtained with 600 ml PCM for 0.2 hour power failure.Therefore, experimental and numerical researches based on PCM integrated refrigeration systems are very important. This type of studies will overcome most of the global and local problems associated with the usage of conventional refrigeration systems.
Keywords: Chemical engineering; Enerji tasarrufu; Faz Değiştiren Madde (FDM); Kimya mühendisliği; Phase Change Material (PCM); Refrigeretion systems; Soğutma sistemleri Energy saving